Validation of stool and blood analysis compared to Inv A and ttr based direct blood qPCR assay as diagnostic tools for typhoid fever - Shymaa A. Elaskary; Hanem Mohamed Badawy; Doaa S. Elgendy; Amany Mohammed Abdelmaksoud; Rasha G. Mostafa (BMC Microbiology)
Abstract Background The development of molecular techniques, such as polymerase chain reaction (qPCR), provides a promising approach for detecting S. enterica due to its rapidity, sensitivity, specificity, and resistance to interference from antibiotics, surpassing the routinely used stool and blood culture methods. Aim This study aims to compare different stool and blood culturing methods with the direct blood qPCR-based assay of Salmonella Invasion A (Inv A) and Salmonella Tetrathionate Respiration (ttr) virulence genes as diagnostic tools for typhoid fever. Method One hundred clinically diagnosed typhoid fever (CDTF) cases were subjected to conventional stool and blood culture, followed by standard biochemical and serotyping identification of S. enterica, compared to direct blood and enriched blood-based ttr and Inv A qPCR-based techniques. Results Using the enriched blood-based ttr and Inv A qPCR technique, 90% and 85% of cases, respectively, were positive and confirmed as typhoid fever. While the blood-based ttr and Inv A qPCR technique showed 82% and 80% positivity, respectively, with a Ct threshold value of 37 cycles for both techniques. The stool culture method revealed S. enterica infection in only 32% of cases, while blood culture methods identified S. enterica in 48% of cases. Conclusion The enriched blood-based ttr and Inv A qPCR method is a promising rapid tool for diagnosing typhoid fever, offering high sensitivity, specificity, accuracy and unaffected by antibiotic intake.